2021
DOI: 10.1021/acs.chemmater.1c00821
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Point Defects by Elastic Strain Modulates Nanoparticle Exsolution on Perovskite Oxides

Abstract: Exsolution generates stable and catalytically active metal nanoparticles via phase precipitation out of a host oxide. An ability to control the size and dispersion of the exsolution particles is desirable for design of nanostructured (electro)catalysts. Here, we demonstrate that tuning point defects by lattice strain affects both the thermodynamics and the kinetics of iron (Fe 0 ) exsolution on La 0.6 Sr 0.4 FeO 3 (LSF) thin film model. By combining in situ surface characterization and ab initio defect modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(120 citation statements)
references
References 73 publications
10
110
0
Order By: Relevance
“…[ 43 ] Moreover, thin‐film LSF has also been employed as model systems to investigate surface exsolution in previous studies. [ 30,37,44 ] We showed that exsolution in such oxide thin films generates not only metal nanoparticles (as in prior work), but also more complex nanostructures with implications for the thin‐film properties; including crystalline Ruddlesden‐Popper (RP) domains and percolated Fe‐deficient nm‐scale channels. These phenomena, to the best of our knowledge, are reported for the first time in LSF.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…[ 43 ] Moreover, thin‐film LSF has also been employed as model systems to investigate surface exsolution in previous studies. [ 30,37,44 ] We showed that exsolution in such oxide thin films generates not only metal nanoparticles (as in prior work), but also more complex nanostructures with implications for the thin‐film properties; including crystalline Ruddlesden‐Popper (RP) domains and percolated Fe‐deficient nm‐scale channels. These phenomena, to the best of our knowledge, are reported for the first time in LSF.…”
Section: Introductionmentioning
confidence: 70%
“…During the heating step, the normalized O 1s intensity gradually decreased (Figure S15, Supporting Information), which indicates oxygen vacancy formation (i.e., lattice reduction). [ 37 ] The Fe 0 species appeared on the surface at 450 °C, which marked the onset of Fe 0 exsolution. Upon further heating in 0.5 Torr H 2 , the surface concentrations of Fe 0 and O* increased synergistically with temperature, indicating an increasing extent of Fe 0 exsolution in the LSF film.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations